THE BIS-GRID ENGINE: AN ORCHESTRATION AS A SERVICE INFRASTRUCTURE - Höing, André; Scherp, Guido; Gudenkauf, Stefan (International Journal of Computing, 2014)
The need for information system integration is typical for many companies including small and medium-sized enterprises (SMEs). But especially for SMEs, the costs to run a full-fledged integration platform in-house are beyond the available IT budget. This article describes the concept of Orchestration as a Service (OaaS), a specialization of the Platform as a Service (PaaS) paradigm in the Cloud (computing) world. The goal of this paradigm is to provide a workflow-based integration platform as a (Cloud) service focusing on so-called service orchestrations. We present the BIS-Grid Engine as a core middleware for an OaaS infrastructure including a discussion about how our solution addresses security requirements that are a key issue in Cloud technologies.